Does the HR 6819 triple system contain a dormant black hole? Not necessarily. (10th July 2020) - Mazeh, Tsevi; Faigler, Simchon
ABSTRACT: A recent paper by Rivinius et al. proposed that HR 6819 is a triple system, with a distant Be star and a binary of 40-d orbit, composed of a B3 III giant and a dormant black hole (BH). We suggest that the evidence for this model is not conclusive. In an alternative model, the companion of the giant is by itself a short-period binary in, say, a ∼4-d orbit, consisting, for example, of two A0 stars. Each of the two A0 stars should contribute 4 per cent of the total brightness of the system in the V band, and their spectral lines are moving due to their assumed orbital motion with an unknown period. Therefore, only a careful analysis of the observed spectra can exclude such a model. Before such an analysis is presented and upper limits for the depths of the hypothetical A0 star absorption lines are derived, the model of a hidden close pair is more probable than the BH model.